2014
DOI: 10.1088/0004-637x/790/1/68
|View full text |Cite
|
Sign up to set email alerts
|

Mass Flows in a Prominence Spine as Observed in Euv

Abstract: We analyze a quiescent prominence observed by the Solar Dynamics Observatory's Atmospheric Imaging Assembly (AIA) with a focus on mass and energy flux in the spine, measured using Lyman continuum absorption. This is the first time this type of analysis has been applied with an emphasis on individual features and fluxes in a quiescent prominence. The prominence, observed on 2010 September 28, is detectable in most AIA wavebands in absorption and/or emission. Flows along the spine exhibit horizontal bands 5 -10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Our Fig. 5a clearly shows that counterstreamings are present in our simulations due to random heating localised at the footpoints, as also suggested by Kucera et al [35]. While Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our Fig. 5a clearly shows that counterstreamings are present in our simulations due to random heating localised at the footpoints, as also suggested by Kucera et al [35]. While Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The counterstreamings were also detected in extreme ultraviolet (EUV) spectral lines, which correspond to plasma with the temperature around 10 5 − 10 6 degrees [refs. 5,[34][35][36][37]. A puzzling characteristic of the EUV counterstreamings is that their velocity can be up to 100 km s −1 [ref .…”
Section: Introductionmentioning
confidence: 99%
“…Using the canonical values of the prominence density (10 −11 to 10 −10 kg m −3 ) (Labrosse et al 2010) and the observed speeds of the prominence surge (10 to 25 km s −1 ), we obtained an energy flux of 10 W m −2 to 1000 W m −2 . This is in the range of energy fluxes that are sufficient to generate and sustain a quiescent corona (Withbroe & Noyes 1977;Kucera et al 2014) around a prominence.…”
Section: Discussionmentioning
confidence: 99%
“…Mass flows of the cool prominence material are observed ubiquitously in prominence threads (see the review by Parenti (2014), and recent observations by Alexander et al (2013); Kucera et al (2014); Diercke et al (2018)). Combined flows in small-scale threads and waves were also detected and studied in solar prominences by Okamoto et al (2007) and in coronal loops with cool prominence material by Ofman & Wang (2008).…”
Section: Introductionmentioning
confidence: 99%